Does Enrichment Improve Well Being in Animals under Human Care? A Case Study of Two Harbor Seals (Phoca Vitulina). Issue 3 (3rd July 2019) - Vaicekauskaite, Ruta; Schneider, Jennifer N.; Delfour, Fabienne
ABSTRACT: Harbor seals in the wild live in a stimulating environment; therefore, nonhuman-animal caretakers have increasingly been using environmental enrichment to improve the well being of seals under human care. The purpose of this study was to evaluate an object-based environmental enrichment program during a four-month period on stimulating exploration and play and improving conspecific social interactions and human–animal relationships (HAR). Zoo staff conducted the environmental enrichment program as part of the animal care program. Seals were given objects haphazardly and were observed for 20 minutes, and seals' responsiveness during training sessions before and after enrichment was assessed. Seals showed interest in objects throughout the study and interacted more times per session with objects during the later months. Seals showed preferences for objects that were suspended in the water column (e.g., rope). Seals did not show more affiliative behavior but did show some aggressive behavior during enrichment sessions in comparison with free-swimming sessions. One seal showed better responsiveness to trainers in training sessions that followed an enrichment session than in other trainings sessions. Overall, the enrichment program was successful in increasing intrinsically motivated behaviors and showed that object-based enrichment has the potential to improve HAR between seals and their trainers.